IMPLEMENTASI ORIENTASI TEKNIS PENDIDIKAN KESETARAAN TERHADAP PENINGKATAN KOMPETENSI PAMONG BELAJAR SKB DALAM MENGELOLA PENDIDIKAN KESETARAAN - Hapsari, Melati Indri (JIV-Jurnal Ilmiah Visi, 2010)
Tutors play an important role in executing Non-formal and Informal Education program at Learning Activities Center, Therefore, technical orientation activities are organized to improve the tutors’ ability to manage equivalency education. This research was conducted to obtain complete data and information needed to present a clear and complete description of the implementation of technical orientation program in P2PNFI Regional II, Semarang. To meet its objective, this research employed mixed method. Quantitative was used to obtain the tutors’ competence in managing equivalency education after they were given technical orientation. Qualitative method was used to describe the implementation of technical orientation in equivalency education. The result of the research indicates the technical orientation program has improved the competence of Learning Activities Center tutors.